Functional Brain Network Connectivity Patterns Associated With Normal Cognition at Old-Age, Local β-amyloid, Tau, and APOE4 - Quevenco, Frances C.; van Bergen, Jiri M.; Treyer, Valerie; Studer, Sandro T.; Kagerer, Sonja M.; Meyer, Rafael; Gietl, Anton F.; Kaufmann, Philipp A.; Nitsch, Roger M.; Hock, Christoph; Unschuld, Paul G. (Frontiers in Aging Neuroscience, 2020)
Background: Integrity of functional brain networks is closely associated with maintained cognitive performance at old age. Consistently, both carrier status of Apoliproprotein E ε4 allele (APOE4), and age-related aggregation of Alzheimers disease (AD) pathology result in altered brain network connectivity. The posterior cingulate and precuneus (PCP) is a node of particular interest due to its role in crucial memory processes. Moreover, the PCP is subject to early aggregation of AD pathology. The current study aimed at characterising brain network properties associated with unimpaired cognition in old aged adults. To determine effects of age-related brain change and genetic risk for AD, pathological proteins ß-amyloid and tau were measured by Positron-emission tomography (PET), PCP connectivity as a proxy of cognitive network integrity, and genetic risk by APOE4 carrier status. Methods: 57 cognitively unimpaired old-aged adults (MMSE=29.20±1.11; 73±8.32 years) were administered 11C Pittsburgh Compound B and 18F Flutemetamol PET for assessing ß-amyloid, and 18F AV-1451 PET for tau. Individual functional connectivity seed maps of the PCP were obtained by resting-state multiband BOLD functional MRI at 3-Tesla for increased temporal resolution. Voxelwise correlations between functional connectivity, ß-amyloid- and tau-PET were explored by Biological Parametric Mapping (BPM). Results: Local ß-amyloid was associated with increased connectivity in frontal and parietal regions of the brain. Tau was linked to increased connectivity in more spatially distributed clusters in frontal, parietal, occipital, temporal, and cerebellar regions. A positive interaction was observable for APOE4 carrier status and functional connectivity with brain regions characterized by increased local ß-amyloid and tau tracer retention. Conclusions: Our data suggest an association between spatially differing connectivity systems and local ß-amyloid and tau aggregates in cognitively normal, old-aged adults, which is moderated by APOE4. Additional longitudinal studies may determine protective connectivity patterns associated with healthy aging trajectories of AD-pathology aggregation.